Укрaинa в системе междунaродных отношений - Әмірхaновa Ә.; Мaкaшевa К. (International relations and international law Journal, 2018)
Problems of modern foreign policy of Ukraine, its relationship with the states in the world. In the early beginning of creation foreign policy of independent Ukraine, its development, formation according to the international standards is reflected in work. The article discusses the impact of foreign policy on the economic development of the state. In addition, in article the comparative analysis of relationship of the state with the different countries, including development of the bilateral relations with the Republic of Kazakhstan is carried out. The article describes the role of Ukraine in the system of international relations and the main Direction of foreign policy of Ukraine. Key words: Kazakhstan, Ukraine, foreign policy, economic policy, international organizations.